2013
DOI: 10.1371/currents.hd.d8917b4862929772c5a2f2a34ef1c201
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional mitochondrial respiration in the striatum of the Huntington’s disease transgenic R6/2 mouse model

Abstract: Metabolic dysfunction and mitochondrial involvement are recognised as part of the pathology in Huntington's Disease (HD). Post-mortem examinations of the striatum from end-stage HD patients have shown a decrease in the in vitro activity of complexes II, III and IV of the electron transport system (ETS). In different models of HD, evidence of enzyme defects have been reported in complex II and complex IV using enzyme assays. However, such assays are highly variable and results have been inconsistent. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 44 publications
(59 reference statements)
4
52
1
Order By: Relevance
“…Consequently, impairment of mitochondrial respiration may affect both oxidative phosphorylation and Ca 2+ uptake. There are several reports suggesting mitochondrial respiratory deficits in various HD models (Tabrizi et al, 2000; Damiano et al, 2013; Aidt et al, 2013). However, our recent studies demonstrated the lack of defects in oxidative metabolism in mitochondria isolated from the whole HD brains and in cultured cortical and striatal neurons derived from HD mice (Hamilton et al, 2015; Hamilton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, impairment of mitochondrial respiration may affect both oxidative phosphorylation and Ca 2+ uptake. There are several reports suggesting mitochondrial respiratory deficits in various HD models (Tabrizi et al, 2000; Damiano et al, 2013; Aidt et al, 2013). However, our recent studies demonstrated the lack of defects in oxidative metabolism in mitochondria isolated from the whole HD brains and in cultured cortical and striatal neurons derived from HD mice (Hamilton et al, 2015; Hamilton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier findings suggested abnormalities in mitochondrial respiration and defects in Ca 2+ handling in mitochondria from HD mouse and cell models (Tabrizi et al, 2000; Damiano et al, 2013; Aidt et al, 2013; Panov et al, 2002; Choo et al, 2004; Lim et al, 2008). In our previous studies, we tested the possible deleterious effects of mHtt on mitochondrial oxidative metabolism and Ca 2+ handling using isolated nonsynaptic and synaptic mitochondria from the whole brain of HD mice (Pellman et al, 2015; Hamilton et al, 2015; Hamilton et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…However, the enzyme itself may be altered following injury devoid of any alteration in mitochondrial content (Chepelev et al, 2009). In addition, flux control ratios were assessed as an internal normalization of the respiratory states to the maximal uncoupler-induced rate of respiration within the ETS, a method that may be independent of tissue heterogeneity (Aidt et al, 2013). All of these methods have strengths and weaknesses, thus we decided to present data for each respiratory state in response to injury multiple ways: tissue mass, FCR, CS activity, as well as ratios for evaluating coupling of respiration to ATP production and the relative contribution of complex I- and II-driven respiration to maximal flux.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome c oxidase (complex IV) is an intracellular measure of oxidative energy metabolic capacity and respiration (72). Complex IV activity is decreased in the mitochondria from both HD patients (14) and HD mice (73). Both VDAC and complex IV are regarded as classic mitochondrial markers, suggesting that AMI treatment has provided considerable mitochondrial support in these mice.…”
Section: Discussionmentioning
confidence: 99%